Investing for the Environment? The Limits of the UN Principles of Responsible Investment. - Gray, T (School of Geography and Environment (University of Oxford), 2009)
International governance is often complicated by collective action problems. This is particularly true in the setting of international environmental governance in which attempts to establish effective international regimes are marred by countless private and public actors with distinct agendas, significant issue uncertainty, and a diversity of non-synchronized initiatives. In light of these difficulties, efforts are underway to embed an international environmental regime within the already developed and, arguably, better understood international regime of global finance. This developing ideology involves financial market participants no longer treating environmental consequences of economic growth as externalities but rather internalizing them as financial risks within their decision-making processes, and is often referred to as responsible investment. The United Nations Principles of Responsible Investment (UN PRI) has played a leading role in these efforts and has benefited significantly from uncritical optimism in doing so. However, an analysis of the UN PRI demonstrates that the organization's lack of transparency, accountability and enforcement actually serve as obstacles to the mainstream adoption of responsible investment practices. The UN PRI, after early successes in legitimizing the responsible investment ideology, appears to be acting as a shroud of legitimacy for traditional 'non-responsible' investment practices. Although the UN PRI may have gained autonomous authority and have diverted from its original goals, the responsible investment ideology retains the promise of being an effective regime to address contemporary environmental change in a world driven by global finance, yet more support from both private and public actors, and corresponding oversight of all actors, is required.